Impact of inadequate conflict management skills on service delivery at Modipe High school in Limpopo Province - Rakgwale, Sebolawe Maria (My University, 2010)
Different studies have clearly defined conflict management but little is known as to whether inadequate conflict management skill is close relative of service delivery. This paper presents the aim and objectives of the study, summary of the methodology used, type of data collected, very brief description of the data analysis methods, summary of findings conclusion and recommendations. The aim of the study is to investigate problems affecting the implementation of conflict management strategies within the school situation as witnessed by the chaotic situation within the school. Hence the concern raised by the community on critical issues which motivate the school management team to improve their knowledge, skills and attitudes on managing conflict in the workplace. The type of data collected was both primary and secondary where people’s views were called upon to provide information on the phenomenon. The objectives of the study are to conduct research on the challenge of conflict management in Modipe High School, to examine the relationship between conflict management and service delivery, to assess the impact of conflict on service delivery and to contribute towards strategic solutions for more effective conflict management. Qualitative research methodology was applied using data collection techniques such as the interviews and questionnaires to draw information about the topic under investigation. Primary and secondary data was collected from interviews, questionnaires and literature review respectively. The data analysis methods that were employed include content and thematic analysis. This was followed by a brief summary. The study revealed that inadequate conflict management skills on service delivery can be caused by various actions, for example, unfair treatment of others, ignorance of work procedures, application of rules and regulations, and self-disciplined educators. To this end, it is recommended that if there is a difference of opinion, proper channel of communication should be followed through the union representatives and supervisors, until the complaints or needs reach the management unit for discussion and finalisation where possible, without disagreements.
Thesis (MPA.)--University of Limpopo, 2010
Keywords: Conflict management skills; Service delivery; 371.2011; School management and organization; Conflict management